A proposed bio-panel to predict risk for spontaneous preterm birth among African American women. Issue 5 (November 2015) - Gillespie, Shannon L.; Christian, Lisa M.; Neal, Jeremy L.
Abstract Preterm birth (PTB), or birth prior to 37 weeks gestation, impacts 11.5% of U.S. deliveries. PTB results in significant morbidity and mortality among affected children and imposes a large societal financial burden. Racial disparities in PTB are alarming. African American women are at more than 1.5 times the risk for PTB than white women. Unfortunately, the medical community's ability to predict who is at risk for PTB is extremely limited. History of a prior PTB remains the strongest predictor during a singleton gestation. Cervical length and fetal fibronectin measurement are helpful tools. However, usefulness is limited, particularly among the 95% of U.S. women currently pregnant and lacking a history of PTB. Therefore, preventive therapies do not reach a great number of women who may benefit from them. This manuscript, in response to the pressing need for predictors of PTB risk and elimination of racial disparities in PTB, presents a proposed bio-panel for use in predicting risk for spontaneous PTB among African American women. This bio-panel, measured each trimester, includes stimulated production of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, IL-1 receptor antagonist (Ra), soluble(s) TNF receptor(R) 1, and sTNFR2, and cortisol responsiveness. We hypothesize that greater IL-1β and TNF-α production, decreased IL-1Ra, sTNFR1, and sTNFR2 production, and decreased cortisol responsiveness at each time point as well as a more expedient alignment with this unfavorable profile over time will be associated with PTB. The choice to focus on inflammatory parameters is supported by data highlighting a crucial role for inflammation in labor. Specific inflammatory mediators have been chosen due to their potential importance in preterm labor among African American women. The bio-panel also focuses on inflammatory regulation (i.e., cytokine production upon ex vivo stimulation), which is hypothesized to provide insight into potential in vivo leukocyte responses and potential for initiation of a preterm inflammatory cascade. Production of receptor antagonists is also considered, as pro-inflammatory mediator effects can be greatly influenced by their balance with respective antagonists. Finally, leukocyte responsiveness to cortisol is included as a measure of cortisol's ability to convey anti-inflammatory signals. The development of a bio-panel predictive of risk for spontaneous PTB among African American women would represent a significant advancement. Available preventive therapies, namely progesterone supplementation, could be delivered to women deemed at risk. Further, the identification of biological predictors of PTB may uncover novel targets for preventive therapies.